SCN2A and Its Related Epileptic Phenotypes - Praticò, Andrea D.; Giallongo, Alessandro; Arrabito, Marta; D'Amico, Silvia; Gauci, Maria Cristina; Lombardo, Giulia; Polizzi, Agata; Falsaperla, Raffaele; Ruggieri, Martino (Journal of Pediatric Neurology, 2021)
Epilepsies due to SCN2A mutations can present with a broad range of phenotypes that are still not fully understood. Clinical characteristics of SNC2A-related epilepsy may vary from neonatal benign epilepsy to early-onset epileptic encephalopathy, including Ohtahara syndrome and West syndrome, and epileptic encephalopathies occurring at later ages (usually within the first 10 years of life). Some patient may present with intellectual disability and/or autism or movement disorders and without epilepsy. The heterogeneity of the phenotypes associated to such genetic mutations does not always allow the clinician to address his suspect on this gene. For this reason, diagnosis is usually made after a multiple gene panel examination through next generation sequencing (NGS) or after whole exome sequencing (WES) or whole genome sequencing (WGS). Subsequently, confirmation by Sanger sequencing can be obtained. Mutations in SCN2A are inherited as an autosomal dominant trait. Most individuals diagnosed with SCN2A–benign familial neonatal-infantile seizures (BFNIS) have an affected parent; however, hypothetically, a child may present SCN2A-BNFNIS as the result of a de novo pathogenic variant. Almost all individuals with SCN2A and severe epileptic encephalopathies have a de novo pathogenic variant. SNC2A-related epilepsies have not shown a clear genotype–phenotype correlation; in some cases, a same variant may lead to different presentations even within the same family and this could be due to other genetic factors or to environmental causes. There is no “standardized” treatment for SCN2A-related epilepsy, as it varies in relation to the clinical presentation and the phenotype of the patient, according to its own gene mutation. Treatment is based mainly on antiepileptic drugs, which include classic wide-spectrum drugs, such as valproic acid, levetiracetam, and lamotrigine. However, specific agents, which act directly modulating the sodium channels activity (phenytoin, carbamazepine, oxcarbamazepine, lamotrigine, and zonisamide), have shown positive result, as other sodium channel blockers (lidocaine and mexiletine) or even other drugs with different targets (phenobarbital).
Keywords: SCN2A; sodium channel; benign familial neonatal seizures; epileptic encephalopathy; autism